Strategi Meningkatkan Lulusan Bermutu di Perguruan Tinggi - Asmawi, M Rosul (UI Scholars Hub, 2005)
Make-Up of education quality in college represent urgency insisting on to is immediately conducted by repair. MakeUp of that quality basically can be conducted with fox strategy of one of the subsistem : human being, structure, technological, and the organizational process. Its bearing with certifiable grad improvement strategy study in college, that change is conducted at subsistem of human being of technology and, covering : (1) student which is educating; (2) lecturer as instructor and educator; and (3) facilities and basic facilities. To get student with best seed, can be conducted with selection system which is only considering quality, non goals of amount of student so that output yielded can be enthused by the stock exchange labour. Lecturer of besides as instructor, at the same time as educator educating candidate ekonom become human being which with good moral as is intention of education. To execute that function, lecturer have to have functional position and improve its ability through education to ladder S2 and or S3 and also various seminar activity and or training. So with facilities and basic facilities, covering practice student in laboratory and or the adequate computerization